2018
DOI: 10.1093/hmg/ddy006
|View full text |Cite
|
Sign up to set email alerts
|

Deep molecular phenotypes link complex disorders and physiological insult to CpG methylation

Abstract: Epigenetic regulation of cellular function provides a mechanism for rapid organismal adaptation to changes in health, lifestyle and environment. Associations of cytosine-guanine di-nucleotide (CpG) methylation with clinical endpoints that overlap with metabolic phenotypes suggest a regulatory role for these CpG sites in the body’s response to disease or environmental stress. We previously identified 20 CpG sites in an epigenome-wide association study (EWAS) with metabolomics that were also associated in recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 74 publications
2
39
0
Order By: Relevance
“…At a stringent Bonferroni level of significance (correction for number of proteins and clinical phenotypes), we identified associations for 14 of the proteins and eight of the CpG sites (Supplementary Data 7 and 8). Finally, we tested the 89 CpG sites for association with 2,251 urinary, salivary, and blood metabolites that we previously reported 15 . We found 20 associations at Bonferroni significance ( p < 2.5 × 10 −7 = 0.05/89/2251) (Supplementary Data 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a stringent Bonferroni level of significance (correction for number of proteins and clinical phenotypes), we identified associations for 14 of the proteins and eight of the CpG sites (Supplementary Data 7 and 8). Finally, we tested the 89 CpG sites for association with 2,251 urinary, salivary, and blood metabolites that we previously reported 15 . We found 20 associations at Bonferroni significance ( p < 2.5 × 10 −7 = 0.05/89/2251) (Supplementary Data 9).…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore essential to account for these driving and potentially confounding factors in an EWAS approach. Complex networks of (co-)associated multi-omics traits, connecting CpG methylation, gene expression, protein, and metabolite levels to disease endpoints then emerge from such EWASs, as we recently showed at the example of a multi-omics association study with a small set of CpG sites 15 . Such networks might eventually guide a more personalized treatment of complex disorders, using for instance DNA methylation as a precise read-out of the body’s disease status with respect to the affected pathways, or to identify drug targets that may allow the modification of the underlying dysregulated processes.…”
Section: Introductionmentioning
confidence: 83%
“…The positive direction of effects observed in identified DNAme–lung function association is in accordance with the reported hypomethylation of smoking-related DNAme sites. The identified lung function-associated CpGs in this study have been previously reported to be associated with smoking-related molecular phenotypes [22], with increased risk of noncommunicable disease, including cancer [20, 23], and with epigenetically defined accelerated ageing [24].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Zaghlool et al 23 aimed at elucidating the molecular pathways of 20 previously established CpG sites by using multi-omics data in 359 samples from the multi-ethnic Qatar Metabolomics Study on Diabetes. We observe associations at nominal significance at six of these 20 sites and demonstrate associations within Model 1 at PHGDH, TXNIP, SLC7A11, CPT1A, MYO5C and ABCG1 through the dissection of multi-phenotype effects within our relatively small study sample ( Table 5).…”
Section: Resultsmentioning
confidence: 99%